A kind of aviation nano composite epoxy coating and preparation method thereof

By introducing modified nano-SiO2 particles and core-shell modified epoxy resin into the epoxy resin, aeronautical nanocomposite epoxy coatings are solved, and the performance problems of traditional epoxy coatings under high and low temperature changes and mechanical impact are achieved. Higher flexibility, impact resistance and high temperature resistance.

CN117511347BActive Publication Date: 2025-02-25INST OF CORROSION SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311635239.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-01
Publication Date
2025-02-25
Estimated Expiration
2043-12-01

AI Technical Summary

Technical Problem

The existing epoxy primer for aircraft skinning shows poor temperature impact resistance and poor low temperature flexibility when facing high and low temperature changes, high-speed airflow and mechanical impact.

Method used

Epoxy resin is used as the main resin, and the modified nano SiO2 particles are grafted into the three-dimensional cross-linking network of the polyurethane curing agent, and combined with the core-shell modified epoxy resin, aeronautical nanocomposite epoxy coating is formed.

Benefits of technology

It significantly improves the flexibility, impact resistance and crack resistance of the coating, improves the low-temperature brittleness, and improves the high-temperature resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004582845310000101
    Figure BDA0004582845310000101
  • Figure BDA0004582845310000111
    Figure BDA0004582845310000111
  • Figure BDA0004582845310000121
    Figure BDA0004582845310000121
Patent Text Reader

Abstract

The present application discloses an aviation nano-composite epoxy coating, which uses epoxy resin as the main resin, is obtained by grafting modified nano-SiO2 particles into a three-dimensional cross-linked network of a polyurethane curing agent, and reacting with a core-shell modified epoxy resin. The present application also provides a method for preparing the aviation nano-composite epoxy coating. The present application can solve the problems of poor temperature shock resistance and poor low-temperature flexibility of epoxy primers used in existing aircraft skins.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional coatings, and in particular to an aviation nano-composite epoxy coating and a preparation method thereof. Background Art

[0002] Epoxy coatings have good adhesion, thermal stability, oil resistance, water resistance, chemical resistance and salt spray resistance, so they are widely used in the aviation field. During the flight of an aircraft, it often faces rapid changes in high and low temperatures, strong impacts from high-speed airflow and air impurity particles, and frequent vibration and deformation of the wings. This requires that the aircraft skin coating, especially the long-term aircraft skin coating, has excellent resistance to high and low temperature changes, low-temperature toughness and impact toughness. However, affected by the structure and curing mechanism of epoxy resin, traditional epoxy coatings have poor impact toughness, poor low-temperature toughness, low elongation at break and poor resistance to high and low temperature alternation. This causes cracks in the aircraft epoxy coating during long-term protection, and filamentary corrosion and rust are very likely to occur at the cracks, and the coating loses its protective and decorative properties, affecting the structural safety and flight safety of the aircraft, causing huge economic losses.

[0003] Chinese invention patent application CN114231100A discloses a skin topcoat for aircraft, its preparation method and application. The coating has excellent high temperature resistance and temperature shock resistance, but no low temperature flexibility and impact flexibility data are reported. Invention patent application CN109021803A discloses a varnish for aircraft skin with excellent weather resistance and toughness and its preparation method. The coating has excellent temperature shock resistance, but no low temperature flexibility and impact flexibility data are reported. Invention patent CN112175502B discloses a chromium-free high solid content polyurethane modified epoxy primer. The coating has excellent impact resistance and temperature shock resistance, but no low temperature flexibility and impact flexibility research. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the purpose of the present application is to provide an aviation nano-composite epoxy coating to solve the problems of poor temperature shock resistance and poor low temperature flexibility of the existing epoxy primer for aircraft skin.

[0005] To solve the above problems, the technical solutions adopted in this application are as follows:

[0006] The embodiment of the present application provides an aviation nano-composite epoxy coating, which uses epoxy resin as the main resin, is obtained by grafting modified nano-SiO2 particles into a three-dimensional cross-linked network of a polyurethane curing agent, and reacting with a core-shell modified epoxy resin.

[0007] As a further alternative, the aviation nanocomposite epoxy coating described in the embodiment of the present application comprises component A and component B;

[0008] The A component includes the following ingredients calculated by mass percentage:

[0009] Epoxy resin 20%-30%,

[0010] Core-shell modified epoxy resin 5%-10%,

[0011] Modified nano-SiO2 particles 1%-3%,

[0012] Anti-rust pigment 10%-15%,

[0013] Corrosion inhibitor 0.5%-2%,

[0014] Pigments and fillers 20%-35%,

[0015] Silane coupling agent 1%-3%,

[0016] Mixed solvent 10%-20%,

[0017] Additives 2%-5%;

[0018] The B component comprises the following ingredients calculated by mass percentage:

[0019] Polyamide curing agent 70%-80%;

[0020] Mixed solvent 20%-30%;

[0021] The added amount of component B is 10%-25% of the weight of component A.

[0022] As a further preferred scheme, the epoxy resin used in the embodiment of the present application is a glycidyl ether modified bisphenol A epoxy resin, and its viscosity at 25°C is 2000-4000cps, which can be specifically selected from one or a mixture of two or more of CGE modified bisphenol A epoxy resin, BGE modified bisphenol A epoxy resin, and C12-C14 modified bisphenol A epoxy resin.

[0023] As a further preferred scheme, the core-shell modified epoxy resin used in the embodiment of the present application is one or more of polyacrylic acid core-shell particle modified epoxy resin, polybutadiene rubber core-shell particle modified epoxy resin, polysulfide rubber core-shell particle modified epoxy resin, polynitrile rubber core-shell particle modified epoxy resin, and silicone core-shell particle modified epoxy resin.

[0024] As a further preferred scheme, the modified anti-rust pigment used in the embodiment of the present application is a high-performance polyphosphate, preferably one or more of aluminum zinc polyphosphate, aluminum strontium polyphosphate, and calcium aluminum silicate polyphosphate; the mixed solvent is two or more of xylene, n-butanol, propylene glycol methyl ether, methyl isobutyl ketone, and methyl ethyl ketone.

[0025] As a further preferred solution, the auxiliary agent described in the embodiment of the present application includes one or more of a defoaming agent, a leveling agent, a dispersant, a thickener and an anti-settling agent.

[0026] As a further preferred solution, the modified nano-SiO2 particles used in the embodiment of the present application are prepared by in-situ modification using a sol-gel method, and the raw materials for preparing the modified nano-SiO2 particles include the following raw materials in mass percentage:

[0027] Silicate 20%-30%, silane coupling agent 2%-4%, long-chain silane coupling agent 15%-20%, solvent 20%-40%, catalyst 0.2%-0.4%, and deionized water as the balance.

[0028] As a further preferred solution, in the embodiments of the present application, the preparation method of the modified nano-SiO2 particles is as follows:

[0029] Dispersion: Disperse the silicate in the solvent, add the catalyst solution and stir to mix evenly;

[0030] Hydrolysis: Slowly add deionized water under stirring to allow hydrolysis reaction;

[0031] Coupling reaction: Then add long-chain alkyl silane coupling agent and epoxy silane coupling agent, add deionized water dropwise during stirring, raise the temperature to the reaction temperature and continue stirring to obtain a uniform and transparent sol;

[0032] Drying: The transparent sol is heated and evaporated to remove the solvent to obtain a gel, and the gel is dried to obtain modified nano-SiO2 particles.

[0033] As a further preferred scheme, when preparing the modified nano-SiO2 particles in the embodiment of the present application, the silicate used is one or more of methyl silicate, ethyl silicate, propyl silicate, and butyl silicate; the catalyst is one or more of glacial acetic acid, hydrochloric acid, and ammonia water; the long-chain silane coupling agent is one or more of hexadecyltrimethoxysilane, octadecyltrimethoxysilane, polyether silane, and alkoxy-terminated polysiloxane; the epoxy silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0034] Furthermore, the present application also provides a method for preparing an aviation nanocomposite epoxy coating.

[0035] Preparation of color paste: Add epoxy resin, mixed solvent, and additives into a dispersion tank, stir and mix evenly, add anti-settling agent, modified nano-SiO2 particles, color fillers, anti-rust pigments and corrosion inhibitors, stir and mix evenly at high speed, grind and disperse, and filter the material until the slurry fineness is ≤10μm to obtain the color paste of aviation nano-composite epoxy coating;

[0036] Preparation of component A: Add the color paste, core-shell modified epoxy resin, silane coupling agent, auxiliary agent and mixed solvent prepared in the above steps into a dispersion tank, and stir and mix evenly to obtain component A.

[0037] Preparation of component B: mixing the modified polyamide curing agent with the mixed solvent, and stirring evenly to obtain component B;

[0038] Mixing step: After mixing the above-mentioned component A and component B, add a mixed solvent to dilute, stir and mix evenly to obtain the aviation nano-composite epoxy coating.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] 1. The aviation nano-composite epoxy coating described in the present application uses modified nano-SiO2 particles with active epoxy groups on their surfaces. During the curing process of the coating, the modified nano-SiO2 particles can be grafted into the three-dimensional cross-linked network of the resin curing agent. On the one hand, the uniformity of the distribution of the nano-SiO2 particles in the coating can be ensured. On the other hand, the nano-SiO2 particles act as a "bridge" and can introduce linear long-chain silanes into the three-dimensional network of the resin curing agent, interact with the core-shell modified epoxy resin, reduce the internal stress of the epoxy coating, enhance the flexibility and impact resistance of the coating, and improve the low-temperature brittleness of the coating.

[0041] 2. In the aviation nano-composite epoxy coating described in this application, the modified nano-SiO2 particles are evenly distributed in the coating. When the coating is impacted, silver streaks are generated to absorb external forces and prevent the generation of cracks in the coating. At the same time, the addition of modified nano-SiO2 particles improves the high temperature resistance of the coating.

[0042] 3. The core-shell modified epoxy resin used in the aviation nano-composite epoxy coating described in this application has a very excellent toughening effect, which can effectively improve the low-temperature brittleness of the epoxy coating, and improve the impact strength and fracture toughness of the coating without reducing the strength and thermal deformation temperature of the coating. It synergizes with nano-SiO2 particles to improve the crack resistance of the coating.

[0043] The present invention is further described in detail below in conjunction with specific implementation modes. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0045] The term "comprising" and other equivalent descriptions involved in the specification and claims of this application are intended to cover non-exclusive inclusions, including both the contents clearly described in the specification and claims, and the steps or units that are not described in the specification and claims but are inherent in the product, method or structure.

[0046] The embodiment of the present application provides an aviation nano-composite epoxy coating, which uses epoxy resin as the main resin, and is obtained by grafting modified nano-SiO2 particles into a three-dimensional cross-linked network of a polyurethane curing agent and reacting with a core-shell modified epoxy resin. The aviation nano-composite epoxy coating described in the embodiment of the present application comprises component A and component B;

[0047] The component A comprises the following ingredients calculated by mass percentage: 20%-30% epoxy resin, 5%-10% core-shell modified epoxy resin, 1%-3% modified nano-SiO2 particles, 10%-15% modified anti-rust pigment, 0.5%-2% corrosion inhibitor, 20%-35% color filler, 1%-3% silane coupling agent, 10%-20% mixed solvent, and 2%-5% additive;

[0048] The B component comprises the following components calculated by mass percentage: 70%-80% of polyamide curing agent; 20%-30% of mixed solvent;

[0049] The added amount of component B is 10%-25% of the weight of component A.

[0050] As a further preferred scheme, the epoxy resin used in the embodiment of the present application is a glycidyl ether modified bisphenol A epoxy resin having a viscosity of 2000-4000cps@25°C, which can be specifically selected from but not limited to cardanol glycidyl ether (CGE) modified bisphenol A epoxy resin or n-butyl glycidyl ether (BGE) modified bisphenol A epoxy resin or polyethylene glycol diglycidyl ether (PEGDGA) modified bisphenol A epoxy resin, and can also be selected from one or a mixture of two or more of C12-C14 modified bisphenol A epoxy resins. Specifically, you can choose the modified bisphenol A epoxy resin with a leveling model KD175×90 or the modified bisphenol A epoxy resin with a leveling model KD176×90 produced by Guodu Company, the modified bisphenol A epoxy resin with a product model EPON872 produced by Hansen Company, the modified bisphenol A epoxy resin with a product model DER732 produced by Dow Company, and the modified bisphenol A epoxy resin with a product model DER736 produced by Dow Company.

[0051] In the present application, the core-shell modified epoxy resin is used as the resin raw material, which is a polymer of multilayer structure, and the core and shell have different functions respectively. The internal stress of the modified epoxy resin of this structure is reduced, and the bonding strength and impact resistance are improved, so it not only has a good toughening effect, but also does not cause a significant loss of thermodynamic properties. In the present application, the low-temperature brittleness of the epoxy coating can be effectively improved by using the core-shell modified epoxy resin, while not reducing the strength and heat deformation temperature of the coating, the impact strength and fracture toughness of the coating are improved, and the core-shell modified epoxy resin and nano-SiO2 particles work together to improve the crack resistance of the coating. The core-shell modified epoxy resin used in some embodiments of the present application is selected from one or more of polyacrylic acid core-shell particle modified epoxy resin, polybutadiene rubber core-shell particle modified epoxy resin, polysulfide rubber core-shell particle modified epoxy resin, polynitrile rubber core-shell particle modified epoxy resin, and silicone core-shell particle modified epoxy resin. Specifically, it can be selected from but not limited to the core-shell modified epoxy resin with product model FORTEGRA352 produced by Dow Chemical, the core-shell modified epoxy resin with product model KR170 produced by Guodu Company, the core-shell modified epoxy resin with product model KR207 produced by Guodu Company, the core-shell modified epoxy resin with product model KR267 produced by Guodu Company, the core-shell modified epoxy resin with product model MX-153 produced by Zhongyuan Company, and the core-shell modified epoxy resin with product model CSR-303 produced by Selvi.

[0052] As a further preferred solution, the anti-rust pigment used in the embodiment of the present application greatly improves the mechanical properties of the coating, especially helps to improve the density and adhesion of the coating, and can delay and prevent the penetration of water, oxygen and chloride ions into the interior of the coating. Preferably, the anti-rust pigment is a polyphosphate. Phosphate can generate phosphate complex salts on the surface of steel, passivate the surface of steel, and thus effectively protect the steel components. In some embodiments of the present application, preferably, the anti-rust pigment is selected from but not limited to one or more of polyphosphate aluminum zinc, polyphosphate aluminum strontium, polyphosphate calcium aluminum silicate; the mixed solvent is two or more of xylene, n-butanol, propylene glycol methyl ether, methyl isobutyl ketone, and methyl ethyl ketone. The auxiliary agent described in the embodiment of the present application includes one or more of auxiliary agents such as defoamers, leveling agents, dispersants, thickeners, and anti-settling agents. The silane coupling agent used in the present application is γ-glycidyloxypropyltrimethoxysilane, specifically selected from one or more of the product model KH-560, the product model A187 produced by Momentive Corporation of the United States, the product model OFS-6040 produced by Shin-Etsu Chemical Co., Ltd. of Japan, the product model KBM-403 produced by Dow Corning Corporation of the United States, and the product model GLYMO produced by Evonik of Germany.

[0053] Further, the corrosion inhibitor used in the embodiments of the present application is an active organic corrosion inhibitor, preferably, the corrosion inhibitor is an organic nitro compound zinc salt. The color filler used in the embodiments of the present application includes a coloring pigment and a physical filler. In some embodiments, preferably, the coloring pigment includes one or more of yellow iron oxide, red iron oxide, rutile titanium dioxide and carbon black; the physical filler is selected from but not limited to one or more of precipitated barium sulfate, mica powder, talcum powder, silica powder and heavy calcium carbonate.

[0054] The modified nano-SiO2 particles used in the present application are modified nano-SiO2 particles obtained after silane modification, and the surface of the modified nano-SiO2 particles has a thicker molecular coating layer, the lipophilicity of the nano-SiO2 particles is improved, the compatibility with organic solvents and epoxy resins is enhanced, the agglomeration of the nano-SiO2 particles is reduced, and its dispersibility in the coating system is improved. The modified nano-SiO2 particles used in the specific embodiments of the present application are prepared by in-situ modification using a sol-gel method, and the raw materials for preparing the modified nano-SiO2 particles include the following raw materials in mass percentage:

[0055] Silicate 20%-30%, silane coupling agent 2%-4%, long-chain silane coupling agent 15%-20%, solvent 20%-40%, catalyst 0.2%-0.4%, and deionized water as the balance.

[0056] In the above scheme, the surface of the modified nano-SiO2 particles contains active epoxy groups. During the curing process of the coating, the modified nano-SiO2 particles can be grafted into the three-dimensional cross-linked network of the resin curing agent, ensuring the uniform distribution of the nano-SiO2 particles in the coating. At the same time, the nano-SiO2 particles play the role of a "bridge", introducing linear long-chain silane into the three-dimensional network of the resin curing agent, and synergizing with the core-shell modified epoxy resin to reduce the internal stress of the epoxy coating, improve the flexibility and impact resistance of the coating, and improve the low-temperature brittleness of the coating. The modified nano-SiO2 particles are evenly distributed in the coating. When the coating is impacted, silver streaks are generated to absorb external forces and prevent the generation of cracks in the coating. At the same time, the addition of modified nano-SiO2 particles improves the high temperature resistance of the coating.

[0057] As a further preferred solution, in the examples of the present application, the preparation method of the modified nano-SiO2 particles described in the examples of the present application is as follows:

[0058] Dispersion: Disperse the silicate in the solvent, add the catalyst solution and stir to mix evenly;

[0059] Hydrolysis: Slowly add deionized water under stirring to allow hydrolysis reaction;

[0060] Coupling reaction: Then add long-chain alkyl silane coupling agent and epoxy silane coupling agent, add deionized water dropwise during stirring, raise the temperature to the reaction temperature and continue stirring to obtain a uniform and transparent sol;

[0061] Drying: The transparent sol is heated and evaporated to remove the solvent to obtain a gel, and the gel is dried to obtain modified nano-SiO2 particles.

[0062] As a further preferred scheme, when preparing the modified nano-SiO2 particles in the embodiment of the present application, the silicate used is one or more of methyl silicate, ethyl silicate, propyl silicate, and butyl silicate; the catalyst is one or more of glacial acetic acid, hydrochloric acid, and ammonia water; the long-chain silane coupling agent is one or more of hexadecyltrimethoxysilane, octadecyltrimethoxysilane, polyether silane, and alkoxy-terminated polysiloxane; the epoxy silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0063] The polyurethane curing agent used in the embodiments of the present application is selected from but not limited to one or more of the curing agent with product model G5221×70 produced by Guodu Company, the curing agent with product model V115 produced by Corning, the curing agent with product model 221×70 produced by Evonik, the curing agent with product model 115-3 produced by Huntsman, the curing agent with product model DEH115 produced by Dow, and the curing agent with product model NT1541 produced by Cardolite.

[0064] Furthermore, the present application also provides a method for preparing an aviation nanocomposite epoxy coating, the method comprising:

[0065] Preparation of color paste: Add epoxy resin, mixed solvent, and additives into a dispersion tank, stir and mix evenly, add anti-settling agent, modified nano-SiO2 particles, pigments and fillers, modified anti-rust pigments, and corrosion inhibitors, stir and mix evenly at high speed, grind and disperse, and filter the material until the slurry fineness is ≤10μm to obtain the color paste of aviation nano-composite epoxy coating;

[0066] Preparation of component A: Add the color paste, modified epoxy resin, silane coupling agent, additives and mixed solvent prepared in the above steps into a dispersion tank, and stir and mix evenly to obtain component A.

[0067] Preparation of component B: mixing the modified polyamide curing agent with the mixed solvent, and stirring evenly to obtain component B;

[0068] Mixing step: After mixing the above-mentioned component A and component B, add a mixed solvent to dilute, stir and mix evenly to obtain the aviation nano-composite epoxy coating.

[0069] The following are specific embodiments of the present application. In the following embodiments, the raw materials used are epoxy resin KD-175ⅹ90 produced by Guodu Company with a viscosity of 25°C / 2500cps, core-shell modified epoxy resin KR-207 produced by Guodu Company, dispersant BYK110 produced by BYK, bentonite SD-2 produced by Deqian Company, defoaming agent BYK A530 produced by BYK, titanium dioxide R706 produced by BYK Chemours, strontium aluminum polyphosphate SRPP produced by Haibo Company, silane coupling agent A187 produced by Momentive Corporation of the United States, leveling agent BYK 358N produced by BYK, and polyamide curing agent V11 produced by Corning.

[0070] Example 1

[0071] This embodiment provides an aviation nano-composite epoxy coating, comprising component A and component B, and the mass percentage of each component is shown in Table 1.

[0072] Table 1

[0073]

[0074]

[0075] The preparation method of the aviation nanocomposite epoxy coating described in this embodiment is as follows:

[0076] (1) Add epoxy resin, a mixed solvent of xylene and n-butanol (volume ratio 1:1), dispersant BYK110, and defoamer BYK A530 into a dispersion tank, stir at a speed of 500 rpm for 15 minutes to mix evenly, add bentonite SD-2 and modified nano-SiO2 particles under stirring, disperse at a speed of 1200 rpm for 20 minutes, and after completely mixing evenly, add titanium dioxide, barium sulfate, talcum powder, mica powder, strontium aluminum polyphosphate, and 5-nitro-zinc meta-benzoate in sequence at a speed of 800 rpm. After the addition is completed, increase the speed to 1500 rpm and disperse for 20 minutes, then add zirconium beads and grind and disperse for 3 hours. When the slurry fineness is ≤10 μm, filter the material to obtain a high-solid aviation nano-composite epoxy coating color paste;

[0077] (2) adding the high solid content aviation nano-composite epoxy coating color paste prepared in the above step into a dispersion tank, and then adding the core-shell modified epoxy resin, silane coupling agent A187, leveling agent BYK 358N and the remaining mixed solvent in sequence under stirring at 800 rpm, increasing the speed to 1200 rpm and dispersing for 30 minutes to obtain component A;

[0078] (3) Add the modified polyamide curing agent, xylene and n-butanol (volume ratio 1:1) mixed solvent into a dispersion tank, and stir at 500 rpm to mix evenly to obtain component B.

[0079] Example 2

[0080] This embodiment provides an aviation nano-composite epoxy coating, comprising component A and component B, and the mass percentage of each component is shown in Table 2.

[0081] Table 2

[0082]

[0083] The preparation method of the aviation nanocomposite epoxy coating described in this embodiment is as follows:

[0084] (1) Add epoxy resin, a mixed solvent of xylene and n-butanol (volume ratio 1:1), dispersant BYK110, and defoamer BYK A530 into a dispersion tank, stir at a speed of 500 rpm for 15 minutes to mix evenly, add bentonite SD-2 and modified nano-SiO2 particles under stirring, disperse at a speed of 1200 rpm for 20 minutes, and after completely mixing evenly, add titanium dioxide, barium sulfate, talcum powder, mica powder, strontium aluminum polyphosphate, and 5-nitro-zinc meta-benzoate in sequence at a speed of 800 rpm. After the addition is completed, increase the speed to 1500 rpm and disperse for 20 minutes, then add zirconium beads and grind and disperse for 3 hours. When the slurry fineness is ≤10 μm, filter the material to obtain the aviation nano-composite epoxy coating color paste;

[0085] (2) adding the aviation nanocomposite epoxy coating color paste prepared in the above step into a dispersion tank, and then sequentially adding the core-shell modified epoxy resin, silane coupling agent A187, leveling agent BYK 358N and the remaining mixed solvent under stirring at 800 rpm, increasing the speed to 1200 rpm and dispersing for 30 minutes to obtain component A;

[0086] (3) Add the modified polyamide curing agent, xylene and n-butanol (volume ratio 1:1) mixed solvent into a dispersion tank, and stir at 500 rpm to mix evenly to obtain component B.

[0087] Comparative Example 1

[0088] This comparative example provides an aviation nano-composite epoxy coating without adding core-shell modified epoxy resin, comprising component A and component B, and the mass percentage of each component is shown in Table 3.

[0089] Table 3

[0090]

[0091] The preparation method of the aviation nanocomposite epoxy coating described in this embodiment is as follows:

[0092] (1) Add epoxy resin, a mixed solvent of xylene and n-butanol (volume ratio 1:1), dispersant BYK110, and defoamer BYK A530 into a dispersion tank, stir at a speed of 500 rpm for 15 minutes to mix evenly, add bentonite SD-2 and modified nano-SiO2 particles under stirring, disperse at a speed of 1200 rpm for 20 minutes, and after completely mixing evenly, add titanium dioxide, barium sulfate, talcum powder, mica powder, strontium aluminum polyphosphate, and 5-nitro-zinc meta-benzoate in sequence at a speed of 800 rpm. After the addition is completed, increase the speed to 1500 rpm and disperse for 20 minutes, then add zirconium beads and grind and disperse for 3 hours. When the slurry fineness is ≤10 μm, filter the material to obtain the aviation nano-composite epoxy coating color paste;

[0093] (2) Add the aviation nano-composite epoxy coating color paste prepared in the above step into a dispersion tank, then add silane coupling agent A187, leveling agent BYK 358N and the remaining mixed solvent in sequence under stirring at 800 rpm, increase the speed to 1200 rpm and disperse for 30 minutes to obtain component A;

[0094] (3) Add the modified polyamide curing agent, xylene and n-butanol (volume ratio 1:1) mixed solvent into a dispersion tank, and stir at 500 rpm to mix evenly to obtain component B.

[0095] Comparative Example 2

[0096] This comparative example provides a method of preparing an aviation epoxy coating using fumed silica R972 produced by Degussa Corporation instead of nano-SiO2 particles. The mass percentage of each component is shown in Table 4.

[0097] Table 4

[0098]

[0099]

[0100] The preparation method of the aviation nanocomposite epoxy coating described in this comparative example 1 is as follows:

[0101] (1) Add epoxy resin, a mixed solvent of xylene and n-butanol (volume ratio 1:1), dispersant BYK110, and defoamer BYK A530 into a dispersion tank, stir at a speed of 500 rpm for 15 minutes to mix evenly, add fumed silica R972 and bentonite SD-2 under stirring, disperse at a speed of 1200 rpm for 20 minutes, and after completely mixing evenly, add titanium dioxide, barium sulfate, talcum powder, mica powder, strontium aluminum polyphosphate, and 5-nitro-zinc meta-benzoate in sequence at a speed of 800 rpm. After the addition is completed, increase the speed to 1500 rpm and disperse for 20 minutes, then add zirconium beads and grind and disperse for 3 hours. When the slurry fineness is ≤10 μm, filter the material to obtain a high-solid aviation epoxy coating color paste;

[0102] (2) Add the high-solid aviation epoxy paint paste prepared in the above step into a dispersion tank, then add silane coupling agent A187, leveling agent BYK 358N and the remaining mixed solvent in sequence under stirring at 800 rpm, increase the speed to 1200 rpm and disperse for 30 minutes to obtain component A;

[0103] (3) Add the modified polyamide curing agent and the mixed solvent into a dispersion tank, and stir and mix them evenly at 500 rpm to obtain component B.

[0104] Performance Testing

[0105] The epoxy coatings obtained in Examples 1-3 and Comparative Example 1 were subjected to performance tests. The test substrate used was a 2A12 aluminum alloy plate of 0.5 mm×70 mm×150 mm. The test method and test items are as follows:

[0106] (1) Low temperature flexibility

[0107] The low temperature flexibility of the epoxy coating prepared by the present invention is tested in accordance with the provisions of GB / T 6742. The test environment temperature is (-51±3)°C, and the test is performed using a type II bending tester, the cylindrical shaft diameter is 25 mm, and the test is observed using a 10x magnifying glass.

[0108] (2) Impact flexibility

[0109] The low temperature flexibility of the epoxy coating prepared by the present invention is tested in accordance with the provisions of ASTM D6905. A 10x magnifying glass is used for observation, and the maximum elongation of the test coating without cracks is recorded.

[0110] (3) Temperature shock resistance

[0111] The low temperature flexibility of the epoxy coating prepared by the present invention is tested in accordance with the provisions of GJB150.5A. The low temperature test temperature is (-55±5)°C, and the holding time is 1 hour; the high temperature test temperature is (70±5)°C, and the holding time is 1 hour. The high and low temperature environment transition time is no more than 1 minute, and one low temperature test and one high temperature test constitute one cycle.

[0112] The performance test results are shown in Table 5.

[0113] Table 5

[0114]

[0115] The test results of Examples 1-3 and comparative examples above show that the addition of modified nano-SiO2 particles can significantly improve the toughness and temperature shock resistance of the epoxy coating; the addition of core-shell modified epoxy resin, synergistically with the nano-SiO2 particles, further improves the low-temperature toughness, impact flexibility and temperature shock resistance of the epoxy coating, which can meet the protection requirements of aircraft skin epoxy primer.

[0116] The components listed in the present invention, as well as the upper and lower limits and interval values ​​of the components of the present invention can realize the present invention, and the embodiments are not listed one by one here. Some specific embodiments are listed above to illustrate the present invention. It is necessary to point out here that the above and below specific embodiments are only used to further illustrate the present invention and do not represent a limitation on the protection scope of the present invention.

Claims

1. An aviation nanocomposite epoxy coating, characterized in that: The coating is obtained by using epoxy resin as the main resin, grafting modified nano-SiO2 particles into the three-dimensional cross-linked network of the polyamide curing agent, and reacting with the core-shell modified epoxy resin; it includes component A and component B; The A component includes the following ingredients calculated by mass percentage: Epoxy resin 20%-30%, Core-shell modified epoxy resin 5%-10%, Modified nano-SiO2 particles 1%-3%, Anti-rust pigment 10%-15%, Corrosion inhibitor 0.5%-2%, Pigments and fillers 20%-35%, Silane coupling agent 1%-3%, Mixed solvent 10%-20%, Additives: 2%-5%; The B component comprises the following ingredients calculated by mass percentage: Polyamide curing agent 70%-80%; Mixed solvent 20%-30%; The amount of component B added is 10%-25% of the weight of component A; The core-shell modified epoxy resin is one or more of polyacrylic acid core-shell particle modified epoxy resin, polybutadiene rubber core-shell particle modified epoxy resin, polysulfide rubber core-shell particle modified epoxy resin, polynitrile rubber core-shell particle modified epoxy resin, and organosilicon core-shell particle modified epoxy resin; The modified nano-SiO2 particles are prepared by in-situ modification using a sol-gel method. The raw materials for preparing the modified nano-SiO2 particles include the following raw materials in terms of mass percentage: Silicate 20%-30%, epoxy silane coupling agent 2%-4%, long-chain silane coupling agent 15%-20%, solvent 20%-40%, catalyst 0.2%-0.4%, balance deionized water; The preparation method of the modified nano-SiO2 particles is as follows: Dispersion: Disperse the silicate in the solvent, add the catalyst solution and stir to mix evenly; Hydrolysis: Slowly add deionized water under stirring to allow hydrolysis reaction; Coupling reaction: Then add long-chain alkyl silane coupling agent and epoxy silane coupling agent, add deionized water dropwise during stirring, raise the temperature to the reaction temperature and continue stirring to obtain a uniform and transparent sol; Drying: The transparent sol is heated and evaporated to remove the solvent to obtain a gel, and the gel is dried to obtain modified nano-SiO2 particles.

2. The aviation nanocomposite epoxy coating according to claim 1, characterized in that: The epoxy resin is glycidyl ether modified bisphenol A epoxy resin, and its viscosity is 2000-4000cps@25°C.

3. The aviation nanocomposite epoxy coating according to claim 1, characterized in that: The anti-rust pigment is one or more of aluminum zinc polyphosphate, aluminum strontium polyphosphate, and calcium aluminum silicate polyphosphate; the mixed solvent is two or more of xylene, n-butanol, propylene glycol methyl ether, methyl isobutyl ketone, and methyl ethyl ketone.

4. The aviation nanocomposite epoxy coating according to claim 1, characterized in that: The auxiliary agent includes one or more of a defoamer, a leveling agent, a dispersant, a thickener and an anti-settling agent.

5. The aviation nanocomposite epoxy coating according to claim 1, characterized in that: During the dispersion process, the silicate is one or more of methyl silicate, ethyl silicate, propyl silicate and butyl silicate; the catalyst is one or more of glacial acetic acid, hydrochloric acid and ammonia water; the long-chain silane coupling agent is one or more of hexadecyltrimethoxysilane, octadecyltrimethoxysilane, polyether silane and alkoxy-terminated polyorganosiloxane; the epoxy silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

6. A method for preparing an aviation nanocomposite epoxy coating according to any one of claims 1 to 5, characterized in that: include Preparation of color paste: Add epoxy resin, mixed solvent, and additives into a dispersion tank, stir and mix evenly, add anti-settling agent, modified nano-SiO2 particles, color fillers, anti-rust pigments and corrosion inhibitors, stir and mix evenly at high speed, grind and disperse, and filter the material until the slurry fineness is ≤10μm to obtain the color paste of aviation nano-composite epoxy coating; Preparation of component A: Add the color paste, core-shell modified epoxy resin, silane coupling agent, auxiliary agent and mixed solvent prepared in the above steps into a dispersion tank, and stir and mix them evenly to obtain component A; Prepare component B: mix the polyamide curing agent and the mixed solvent, and stir evenly to obtain component B; Mixing step: After mixing the above-mentioned component A and component B, add a mixed solvent to dilute, stir and mix evenly to obtain the aviation nano-composite epoxy coating.

Citation Information

Patent Citations

  • Varnish for aircraft sheath with excellent weather resistance and toughness and preparation method thereof

    CN109021803A

  • A chromium-free, high-solids-content polyurethane-modified epoxy primer

    CN112175502B

  • Skin finish paint for airplane as well as preparation method and application of skin finish paint

    CN114231100A

  • Wear-resistant anticorrosive paint for polar ships and preparation method thereof

    CN110903734A

  • Adiabetic panels adhesive epoxy resins for membrane type liquid natural gas tank

    KR100689086B1